Teachers’ Perceptions of Critical Pedagogy in English Language Teaching Classroom - Kadel, Purna Bahadur (Journal of NELTA, 2020)
Critical pedagogy practices are rarely followed in the traditional English Language Teaching (ELT) classes in which the focus is on transmitting knowledge to the learners, rather than transforming it. This study is an attempt to explore teachers’ experiences in and their perceptions of the existing practices of critical pedagogy and on its usefulness in ELT classrooms. This is qualitative research in which phenomenological research design was adopted to accomplish this study. Six respondents were selected from three secondary schools of Kathmandu district as a sample through a purposive non-random sampling procedure. In-depth-interview was used as a tool to assemble the required data to answer the research questions of this study. The findings of the study show that the ELT classroom in the district is teacher-directed but not learner-centered; the textbooks, teaching strategies, and methods are partially focused on marginalized groups and underprivileged learners. The ELT practices at the secondary level do not address multiple intelligences; and critical pedagogy is not adopted for the elevation of the marginalized learners though the teachers are aware of its usefulness.